Pengaruh Penggunaan Belimbing Wuluh (Averrhoa Bilimbi) Sebagai Acidifier Terhadap Berat Darah, Berat Bulu, dan Berat Kepala Ayam Broiler - Yuliana Kolo (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2024)
This study aims to determine the effect of Averrhoa Bilimbi as an acidifier on blood weight, feather-weight, and head weight of broiler chickens. The research used 240 DOC, which were put into 24 units and kept until they were 35 days old. The parameters measured were blood weight, feather weight, and head weight. The experiment was carried out experimentally, the experimental design used was a Completely Randomized Design (CRD) with 4 treatments and 6 replications, where there were 24 experimental units, namely as follows: P0 = 1000 ml drinking water, P1 = 900 ml drinking water + 50 ml Averrhoa Bilimbi, P2 = 925 ml drinking water + 75 ml Averrhoa Bilimbi and P3 = 900 ml drinking water + 100 ml Averrhoa Bilimbi. The results showed significant differences (p<0.05) in blood weight, featherweight, and head weight. The conclusion of This research concludes that adding Averrhoa Bilimbi to drinking water can affect blood weight, feather weight, and head weight.